2012
DOI: 10.1100/2012/621969
|View full text |Cite
|
Sign up to set email alerts
|

TNF-αPromotes IFN-γ-Induced CD40 Expression and Antigen Process in Myb-Transformed Hematological Cells

Abstract: Tumour necrosis factor-α, interferon-γand interleukin-4 are critical cytokines in regulating the immune responses against infections and tumours. In this study, we investigated the effects of three cytokines on CD40 expression in Myb-transformed hematological cells and their regulatory roles in promoting these cells into dendritic cells. We observed that both interleukin-4 and interferon-γincreased CD40 expression in these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
2
6
0
Order By: Relevance
“…Tnfrsf1a and Tnfrsf1b were the 6 th and 50 th lowest β scores in the CD40 screen, respectively. Previous studies suggested that TNF stimulation enhances IFNγ-mediated CD40 expression in hematopoietic progenitors (80), and we confirmed this observation in macrophages (Figure 1E). We observed a 6-fold higher induction of CD40 in macrophages stimulated with a combination of IFNγ and TNF compared to IFNγ alone.…”
Section: Resultssupporting
confidence: 90%
“…Tnfrsf1a and Tnfrsf1b were the 6 th and 50 th lowest β scores in the CD40 screen, respectively. Previous studies suggested that TNF stimulation enhances IFNγ-mediated CD40 expression in hematopoietic progenitors (80), and we confirmed this observation in macrophages (Figure 1E). We observed a 6-fold higher induction of CD40 in macrophages stimulated with a combination of IFNγ and TNF compared to IFNγ alone.…”
Section: Resultssupporting
confidence: 90%
“…This result indicated that NKT cells are required for the activation of DCs, and the activation requires both a membrane-bound and a soluble factor. DCs and NKT cells can activate each other reciprocally through CD40-CD40-L binding, and IFNg increases CD40 expression by DCs (30). Results from the CD40-L blockade experiment confirmed that this molecule plays a critical role in the activation phase of the immune response.…”
Section: Discussionsupporting
confidence: 62%
“…Cells treated with 5μg/ml insulin and 20 μg/ml EGF alone for 7 days served as controls. Extraction of membrane protein was as previously described with minor modifications [29]. Briefly, cells were harvested by centrifugation and re-suspended in homogenization buffer and were sonicated for 20 s on ice.…”
Section: Methodsmentioning
confidence: 99%